A Comprehensive Study of Islamic Law and Gender Equality regarding Matchmaking Traditions in Madura - Maskanah Maskanah; Ita Rodiah (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2024)
This research seeks to review the practice of arranged marriages, especially for women, which has become a habit in Madurese society. The method used was observation and interviews with the Rongdurin Village Community, Tanah Merah, Bangkalan (Madura). Data analysis was carried out using two approaches, namely Islamic law with the Saddu al-Dzari’ah framework and gender analysis in the women’s transformation movement. The results show that the initial motive for the practice of arranged marriages is implementing Islamic law and preserving culture, which can bring benefits. However, when the element of coercion is dominant in the matchmaking process, there is great potential for harm. Gender analysis also shows injustice as subordination, negative stereotypes and violence. Even though it is wrapped in religion and culture, injustice and damage (mudharat) must be avoided and eliminated.